2018
DOI: 10.1038/s41598-018-22360-3
|View full text |Cite
|
Sign up to set email alerts
|

Retinal microvascular parameters are not associated with reduced renal function in a study of individuals with type 2 diabetes

Abstract: The eye provides an opportunistic “window” to view the microcirculation. There is published evidence of an association between retinal microvascular calibre and renal function measured by estimated glomerular filtration rate (eGFR) in individuals with diabetes mellitus. Beyond vascular calibre, few studies have considered other microvascular geometrical features. Here we report novel null findings for measures of vascular spread (vessel fractal dimension), tortuosity, and branching patterns and their relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 53 publications
0
16
1
Order By: Relevance
“…Several cross-sectional studies have previously reported associations between RMPs and renal dysfunction [16,18,39,40] including arteriolar narrowing in those with eGFR < 60 mL/min/1.73m 2 [41,42]. In contrast, other studies have failed to detect associations between RMPs and renal function [43,44]. We failed to detect any associations between CRAE and CKD stages 3-5 defined as eGFR < 60 mL/min/1.73m 2 .…”
Section: Discussioncontrasting
confidence: 63%
“…Several cross-sectional studies have previously reported associations between RMPs and renal dysfunction [16,18,39,40] including arteriolar narrowing in those with eGFR < 60 mL/min/1.73m 2 [41,42]. In contrast, other studies have failed to detect associations between RMPs and renal function [43,44]. We failed to detect any associations between CRAE and CKD stages 3-5 defined as eGFR < 60 mL/min/1.73m 2 .…”
Section: Discussioncontrasting
confidence: 63%
“…[22][23][24][25][26][27][28][29][30][31][32][33] However, the findings reported have not always been consistent. 34,35 Therefore, this meta-analysis of cross-sectional studies sought to address the hypothesis that retinal arteriolar and venular calibers are associated with CKD stages 3-5 (eGFR < 60 mL/min/1.73m 2 ) in the general population.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…73 In contrast, large studies of both diabetic and nondiabetic CKD found no relationship between either baseline or change in Df and the presence or progression of CKD (Table 2). 69,74 The lack of a consistent retinal vascular metric for the detection of incident and prevalent CKD may reflect the heterogeneity of the study populations, underlying etiologies, metabolic abnormalities, and treatments, such as immunosuppression and erythropoietin-stimulating agents. It may also suggest that retinal photography has limited sensitivity to reveal a reliable metric among these competing influences.…”
Section: The Retinal Circulation: Cvd Risk Factors and Outcomesmentioning
confidence: 99%